VOLUME INFARK SEBAGAI PREDIKTOR KEJADIAN PNEUMONIA PADA STROKE ISKEMIK AKUT - , dr. Paulina Thiomas Ulita ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background Stroke patients are susceptible to many complications. The most common complication in acute phase of stroke is infection. Stroke-associated infection (SAI) defines as infection that occurs in the first 7 days after stroke onset. The most frequent infection complication is pneumonia. Many researcher had tried to identify clinical variables that have close relation to the risk of pneumonia in acute stroke. The aim of this study is to determine whether infarct volume associated with the occurrence of pneumonia in acute phase of ischemic stroke. Methods This study used a cohort prospective study design. The subjects of this study came from acute (<72 hours) ischemic stroke patients hospitalized in stroke unit and neurologic ward and followed until day 4 - 7 for the occurrence of pneumonia. Statistical analysis for each variable is using Chi-square test and t test when appropriate for univariate analysis then followed by logistic regression for multivariate analyses. Result We obtained 46 patients as study subjects, comprised into 23 subjects in small (â¤20 cc) infarct volume group and 23 subjects in large (>20 cc) group. Pneumonia occurred in 12 (52,2%) subjects with large infarct volume. Large infarction volume is a significant risk factor for pneumonia with RR 5.18 than small volume (p=0.013